Rigorous evaluation of a substance use and teen pregnancy prevention program for American Indian girls and their female caregivers: a study protocol for a randomized controlled trial - Rachel A. Chambers; Jaime Begay; Hima Patel; Jennifer Richards; Danielle Nelson; Summer Rosenstock; Ronni Huskon; Kristin Mitchell; Tiffani Begay; Lauren Tingey (BMC, 2021)
Abstract Background Early sexual initiation is associated with higher risk for sexually transmitted infection, teen pregnancy, domestic violence and substance use in later adolescence and early adulthood. Native American adolescents are more likely to have early sexual initiation compared to other racial/ethnic groups. Few programs designed with and for Native adolescents to delay sexual initiation and substance use have been tested through rigorous evaluations. This is the protocol for the randomized controlled trial of the Asdzáán Be'eena' program, a teen pregnancy and substance use prevention program for young Native girls and their female caregivers. Methods N = 410 female adolescents ages 10-14 and their female caregivers will be enrolled in the study and randomized to the intervention or control arm. The intervention consists of the 11-session Asdzáán Be'eena' program. The control arm consists of mailed non-monetary incentives. All participants will complete evaluations at baseline and 3 follow-up timepoints (immediate, 6 and 12 months post intervention). Evaluations include measures to assess protective factors associated with delayed sexual initiation and substance use. Discussion This is one of the first rigorous evaluations of a gender-specific, culturally tailored teen pregnancy and substance use primary prevention program for Native girls and their female caregivers. If proven efficacious, Native communities will have a culturally appropriate program for promoting protective factors associated with delayed substance use and sexual risk taking. Trial registration NCT04863729 ; April 27, 2021.